Computational Insights into the Antifungal Mechanisms of Coumarin and Hexanol from Ageratum conyzoides and Cyperus rotundus Against Colletotrichum spp - Febryani, Noor; Benatar, Gilang Vaza; Hartini, Elya; Yulianto, Yanto; Hodiyah, Ida; Ridwan, Nur Fathurahman (Jurnal Biologi Tropis, 2026)
Chili anthracnose, caused by Colletotrichum spp., remains a major threat to crop productivity and fruit quality worldwide. The increasing resistance of fungal pathogens to synthetic fungicides highlights the need for sustainable, plant-based alternatives. This study provides computational insights into the antifungal mechanisms of coumarin and hexanol, two major bioactive compounds derived from Ageratum conyzoides and Cyperus rotundus. Molecular docking and molecular dynamics simulations were employed to examine the interactions of these compounds with key Colletotrichum proteins, including calmodulin, PETFP cutinase complex, and chitin deacetylase. The docking results revealed that coumarin exhibited stronger binding affinities and more stable conformations within the enzyme active sites than hexanol, forming multiple hydrogen bonds and π–π stacking interactions with catalytic residues. Molecular dynamics analyses further confirmed the structural stability and compactness of coumarin–protein complexes, indicating its potential to disrupt fungal enzymatic functions critical for pathogenicity. These findings suggest that coumarin, in particular, may serve as a promising lead compound for the development of eco-friendly antifungal agents. The study contributes to a molecular-level understanding of plant-derived antifungal mechanisms, supporting future research into the rational design and optimization of biofungicides for sustainable agriculture.